Ameliorative Effects of Zinc Oxide, in Either Conventional or Nanoformulation, Against Bisphenol A Toxicity on Reproductive Performance, Oxidative Status, Gene Expression and Histopathology in Adult Male Rats - Dina M. M. H. El-Kossi; Shawky S. Ibrahim; Kamel M. A. Hassanin; Nashwa Hamad; Noha A. Rashed; Ahmed Abdel-Wahab (Biological Trace Element Research, 2024)
Bisphenol A (BPA) is a widely used endocrine disruptor that represents a significant risk to male reproductive function. Zinc (Zn) is vital for appropriate development of testes and to guarantee optimal testicular function and spermatogenesis. Our goal was to investigate if zinc oxide (ZnO), either in conventional or nanoformulation, could safeguard adult male rats’ reproductive performance against the damaging effects of BPA. Signaling expression of CYP11A1 and Nrf-2 in the testis, testicular oxidant-antioxidant status, Bax/Bcl-2 apoptotic ratio, and histological examination of various reproductive organs were all evaluated. Twenty-eight adult male albino rats were divided randomly into 4 groups (7 animals each) including the control, BPA, conventional zinc oxide (cZnO) + BPA, and zinc oxide nanoparticles (ZnO-NPs) + BPA groups. The study was extended for 2 successive months. Our findings revealed strong negative effects of BPA on sperm cell characteristics such as sperm motility, viability, concentration and abnormalities. Additionally, BPA reduced serum levels of testosterone, triiodothyronine (T3), and thyroxine (T4). Also, it evoked marked oxidative stress in the testes; elevating malondialdehyde (MDA) and reducing total antioxidant capacity (TAC). BPA significantly downregulated testicular mRNA relative expression levels of CYP11A1 and Nrf-2 , compared to control. Testicular apoptosis was also prompted by increasing Bax/ Bcl-2 ratio in testicular tissue. Histopathological findings in the testes, epididymis, prostate gland, and seminal vesicle confirmed the detrimental effects of BPA. Interestingly, cZnO and ZnO-NPs significantly alleviated all negative effects of BPA, but ZnO-NPs performed better. In conclusion, our findings point to ZnO, specifically ZnO-NPs, as a viable treatment for BPA-induced testicular dysfunction.

New bithiophene derivative attenuated Alzheimer’s disease induced by aluminum in a rat model via antioxidant activity and restoration of neuronal and synaptic transmission - Kholoud AbdEl-Raouf; Hussein S.H. Farrag; Rashed Rashed; Mohamed A. Ismail; Monir A. El-Ganzuri; Wael M. El-Sayed (Journal of Trace Elements in Medicine and Biology, 2024)

Treatment of hepatitis C virus infection with direct-acting antivirals plus ribavirin eliminates viral RNA from peripheral blood mononuclear cells and reduces virologic relapse in diverse hepatic parenchymal changes - Mohamed Darwish Ahmed Abd Alla; Reham M. Dawood; Hassan Abd EL-Hafeth Rashed; Galal Farrag; Islam Abdelmawla Emran Ammar; Mohamed Mahmoud Abdel-Halim Mahmoud; Ghada M. Salum; Ahmed Mohamed Abdulhamid Altanbouly; Mai A. El Meguid; Mostafa K. El Awady (Archives of Virology, 2021)

Repurposing of Secukinumab as Neuroprotective in Cuprizone-Induced Multiple Sclerosis Experimental Model via Inhibition of Oxidative, Inflammatory, and Neurodegenerative Signaling - Amany El-Shahawy Abdel-Maged; Amany M. Gad; Laila Ahmed Rashed; Samar S. Azab; Eman A. Mohamed; Azza S. Awad (Molecular Neurobiology, 2020)

Petrology, geochemistry and remote sensing data of island arc assemblage along Wadi Abu Marawat, Central Eastern Desert, Egypt - A. M. Asran; R. Kh. Bekir; E. Abdel Rahman; A. Abdel El-Rashed (Arabian Journal of Geosciences, 2013)